Acute Kidney Injury in Critically Ill Children Is Not all Acute: Lessons Over the Last 5 Years - Hessey, Erin; Melhem, Nabil; Alobaidi, Rashid; Ulrich, Emma; Morgan, Catherine; Bagshaw, Sean M.; Sinha, Manish D. (Frontiers in Pediatrics, 2021)
Acute kidney injury (AKI) in the pediatric intensive care unit (PICU) is an important risk factor for increased morbidity and mortality during hospitalization. Over the past decade, accumulating data in children and young people have demonstrated that acute episodes of kidney dysfunction can have lasting consequences on multiple organ systems and health outcomes. To date there are no guidelines for follow-up of surviving children that may be at risk of long-term sequalae following AKI in the PICU. The aim of this narrative review is to describe the current literature from the last 5 years on the risk of medium and long-term kidney and non-kidney outcomes after AKI in the PICU. More specifically, we will focus on outcomes in children and young people following AKI in the general PICU population and in children undergoing cardiac surgery. These outcomes include mortality, hypertension, proteinuria, chronic kidney disease, and healthcare utilization. We also aim to highlight the current gaps in knowledge in medium and long-term outcomes in this pediatric population. We suggest a framework for what future research is needed to develop evidence-based guidelines for follow-up of children surviving their episode of critical illness and AKI.